Typology of Users of Psychedelics and Alike Psychoactive Substances in Czechia: Results of the National Online Survey - Kňažek, Filip; Horák, Miroslav; Ocetková, Tereza; Somerlíková, Kristína; Bláhová, Barbora; Plevková, Michaela; Mravčík, Viktor; Chomynová, Pavla; Kočárová, Rita (Journal of psychoactive drugs, 2023)
The aim of this study was to define the typical groups of users of psychedelics and alike psychoactive substances in Czechia regarding various variables such as demographics, their patterns of use, or motivation for use. Data from 890 Czech respondents were collected through an online questionnaire as a part of The National Psychedelic Research Project. Subjects reported experience with the use of 29 selected substances by answering 133 questions of the questionnaire. Cluster analysis based on answers on last year use was performed, and descriptive statistics was used for 18 questions from the questionnaire. Six groups of users were identified with distinguished users and demographic characteristics, namely, The most experienced; Pure smokers; Highly educated mild users; Past-time users with families; Responsible (party) students and Deep meaning natural substance users. Groups differ mainly in the type of substances used, frequency of use last year, and demographics. Our findings highlight several patterns typical for psychedelics and alike psychoactive substances use in Czechia in each of the groups and the need for targeted drug prevention services, the raise of public awareness regarding this topic, and a possible reevaluation of the legal status of some substances. Results can be useful for health-care providers, social workers, and policy-makers.
Keywords: poruchy spojené s užíváním psychoaktivních látek; průzkumy a dotazníky; Surveys and Questionnaires; Substance-Related Disorders; Drug Users; Humans; Česká republika; halucinogeny; lidé; uživatelé drog; Hallucinogens; Czech Republic